Biological debridement combined with stem cell therapy will be a convenient and efficient method for treating chronic wounds in the future. (September 2022) - Song, Mingzhi; Zong, Junwei; Zou, Linxuan; Fu, Zhuodong; Liu, Jing; Wang, Shouyu
Abstract: Chronic wounds have become an epidemic disease, causing treatment difficulties worldwide. The prognosis of chronic wounds is poor, and they can easily cause amputation or even death without timely treatment. Although this is an ancient disease, there is still a lack of effective methods for treating chronic wounds. Here, we propose and introduce a new combination therapy that consist of biological debridement and stem cell therapy. Although there are still some details to be discussed before formal application, the combination of the two methods will undoubtedly become a potential therapeutic method that has the characteristics of extensive source, biological intelligence, safety and high efficiency.